Economic order quantity: an approach in improving inventory management / Mohd Azrai Naim Mohd Mawardi, Nurmuslimah Kamilah Abdullah and Ruzaidah Sulong @ A. Rashid - Mohd Mawardi, Mohd Azrai Naim; Abdullah, Nurmuslimah Kamilah; Sulong @ A. Rashid, Ruzaidah (2013)
A basic research was conducted at a Routine Maintenance Company in East Coast of Peninsula Malaysia regards to inventory management discipline that focused on one high draw item, which is fluorescent lamp PLL 36 watt. This study was aimed to determine the EOQ, total annual inventory cost, number of orders and expected time between orders. It was found that the EOQ for the item was 518 units per order, at RM 43483.60 of total inventory cost with 6 times of order per year and 52 days of expected time between orders. It was recommended to the company to identify the inventory cost for the current practice and make a comparison with the finding of the study. On top of that the management has to consider specific assumptions before they proceed to the total implementation of EOQ in the future. An ABC analysis should be done to their inventory items in strategizing the company’s inventory management system.